Preparation method of polyester resin coating for improving adhesive force of film
By introducing sulfonic acid groups and nanofillers into the polyester resin, the problem of degradation of material properties when improving adhesion is solved in the prior art polyester resin coatings, and the effect of higher adhesion and better mechanical properties is achieved.
Patent Information
- Application Number
- CN202411952431.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-27
AI Technical Summary
When existing polyester resin coatings improve film adhesion, they may lead to a decrease in the flexibility and impact resistance of the material, affecting the overall performance of the film.
By using terephthalic acid and polyol as the hard segments of polyester resin and polyethylene glycol and adipic acid as the flexible segments, the molecular structure of the polyester resin is reasonably designed, the sulfonic acid group is introduced to improve adhesion, and the surface roughness, balanced hardness and flexibility are increased by the addition of nanofillers.
It is realized that while maintaining a certain strength, the adhesion of the film is significantly improved, and the mechanical properties and thermal stability of the material are improved.
Smart Images

Figure BDA0005215163220000081 
Figure BDA0005215163220000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a method for preparing a polyester resin coating for improving film adhesion. Background Art
[0002] Polyester resin is an important class of synthetic polymer materials, widely used in coatings, fibers, plastics and composite materials. Its basic structure consists of ester bonds formed by polycondensation of dibasic acids and polyols, and has good mechanical properties, chemical resistance and thermal stability. Polyester resins can be divided into saturated polyesters and unsaturated polyesters according to their uses and performance requirements. Saturated polyesters are commonly used in coatings and thermoplastic applications, while unsaturated polyesters are widely used in glass fiber reinforced plastics and casting resins. The molecular structure of polyester resins can be optimized to meet specific application requirements by adjusting the ratio of hard segments and soft segments, introducing different types of polyols and acids, and adding crosslinkers and fillers.
[0003] Film materials play a key role in industries such as packaging, electronics, construction and automobiles. In order to ensure the functionality and durability of the film in these applications, the adhesion of the film surface to other materials is crucial, especially for low surface energy films made of materials such as PE, PP, and PET, which need to improve surface adhesion. Polyester resin coatings are ideal for improving film adhesion due to their excellent mechanical properties and chemical stability. First, the molecular structure of polyester resin can be chemically and physically modified to enhance the interfacial bonding between the film and the resin. Secondly, the thermoplastic characteristics of polyester resin allow it to form a good physical anchor with the substrate surface during processing. In addition, polyester resin can form a three-dimensional network structure through cross-linking reaction, further improving the chemical bonding between the film and the resin. By rationally designing the molecular structure and processing technology of polyester resin, the adhesion of the film can be significantly improved, thereby enhancing its performance in harsh environments.
[0004] Although polyester resin coatings have significant advantages in improving film adhesion, the existing technology still has some shortcomings. The traditional polyester resin coating formula may reduce the flexibility and impact resistance of the material while improving adhesion, affecting the overall performance of the film. Summary of the invention
[0005] The present invention relates to a method for preparing a polyester resin coating for improving film adhesion, and belongs to the technical field of polymer materials. The present invention uses terephthalic acid and polyol as the hard segment of the polyester resin, polyethylene glycol and adipic acid as the soft segment, and achieves a good balance between hardness and flexibility through proportioning, so that the resin coating has both certain strength and better adhesion; introduces a strong polar group sulfonic acid group into the hard segment of the polyester resin to improve the adhesion between the polyester film and the substrate; and further improves the adhesion by adding fillers to increase the surface roughness.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a polyester resin coating for improving film adhesion comprises the following steps:
[0008] (1) adding a hard segment monomer and a soft segment monomer into a reaction kettle respectively, adding an esterification catalyst and heating to 180-220° C. to carry out an esterification reaction for 3-8 hours to form a hard segment prepolymer and a soft segment prepolymer respectively;
[0009] (2) adding a polycondensation catalyst to the hard segment prepolymer and the soft segment prepolymer, mixing them uniformly in a vacuum, and heating them to 230-280° C. for polycondensation for 4-10 hours to form a polyester resin;
[0010] (3) cooling to 120-150° C., adding fillers and solvents, ultrasonically treating and stirring for 30-60 minutes to form a polyester resin coating;
[0011] As a preferred technical solution of the present invention, the mass ratio of the hard segment monomer, the soft segment monomer, the esterification catalyst, the polycondensation catalyst and the filler is 20-40:45-65:0.1-1:0.1-1:4-8.
[0012] As a preferred technical solution of the present invention, the hard segment monomers in step (1) are terephthalic acid, sulfonated terephthalic acid and diol; the sulfonated terephthalic acid is sodium 5-sulfoisophthalate, and the diol is one of ethylene glycol, 1,4-butanediol and neopentyl glycol; the mass ratio of terephthalic acid, sulfonated terephthalic acid and diol is 1:0.2-0.4:0.6-0.9.
[0013] As a preferred technical solution of the present invention, the soft segment monomers in step (1) are polyethylene glycol and adipic acid; the mass ratio of the polyethylene glycol to adipic acid is 1:0.08-0.15.
[0014] As a preferred technical solution of the present invention, the esterification catalyst in step (1) is one of 98% concentrated sulfuric acid, p-toluenesulfonic acid and phosphoric acid.
[0015] As a preferred technical solution of the present invention, during the esterification reaction in step (1), water produced by the reaction is continuously removed by vacuum distillation or by using a water separator to promote the esterification reaction.
[0016] As a preferred technical solution of the present invention, the polycondensation catalyst in step (2) is one of Sb2O3, Sb(Ac)3, ethylene glycol antimony, and GeO2; and the vacuum pressure is 100-1000Pa.
[0017] As a preferred technical solution of the present invention, the filler in step (3) is nano-silicon dioxide or nano-zinc oxide; the solvent is one or more of toluene, acetone, butanone, and butyl acetate.
[0018] Beneficial effects of the present invention:
[0019] (1) The present invention uses terephthalic acid and polyol as the hard segment of the polyester resin, and polyethylene glycol and adipic acid as the soft segment. Terephthalic acid has a rigid benzene ring structure, which can provide high mechanical strength and thermal stability; polyethylene glycol has a flexible chain segment, which can provide good flexibility and impact strength. Through reasonable design and optimization, the polyester resin achieves a good balance between hardness and flexibility, so that the polyester resin coating has both certain strength and better adhesion.
[0020] (2) The present invention introduces sulfonic acid groups into the hard segment of the polyester resin. The sulfonic acid groups are strongly polar groups with high electron affinity, and can form a strong bond with the polar functional groups on the surface of polar film substrates (such as PET, PVC, and PI film materials) through hydrogen bonds or dipole-dipole interactions; and improve the hydrophilicity and surface of the polyester resin coating. The coating with good wettability is easier to spread on the surface of the film substrate, thereby increasing the interface contact area and helping to form a stronger adhesion effect; the sulfonic acid groups may ionize in a solution or a humid environment (such as Na in -COONa + and -COO - ), its negatively charged nature can generate electrostatic attraction with the positively charged substrate surface, and on the surface of some non-polar film substrates (such as PE, PP film materials), it improves the adhesion between the polyester resin coating and the film substrate.
[0021] (3) The present invention not only further improves the adhesion but also improves the mechanical properties and thermal stability of the material by adding filler nano-silicon dioxide or nano-zinc oxide, increasing the surface roughness and providing more physical anchoring points. DETAILED DESCRIPTION
[0022] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0023] In the following examples and comparative examples, the polyethylene glycol was purchased from Hai'an Petrochemical Plant in Jiangsu Province, with the model number of PEG-1500; silicon dioxide was purchased from Neo Nano Technology Co., Ltd., with a particle size of 50 nm; and zinc oxide was purchased from Baoheng Chemical Technology Co., Ltd.
[0024] Example 1
[0025] A method for preparing a polyester resin coating for improving film adhesion comprises the following steps:
[0026] (1) adding a hard segment monomer and a soft segment monomer into a reaction kettle respectively, adding an esterification catalyst and heating to 200° C. to carry out an esterification reaction for 5 hours to form a hard segment prepolymer and a soft segment prepolymer respectively;
[0027] (2) adding a polycondensation catalyst to the hard segment prepolymer and the soft segment prepolymer, mixing them uniformly in a vacuum, and heating them to 250° C. for polycondensation for 6 hours to form a polyester resin;
[0028] (3) cooling to 135° C., adding fillers and solvents, ultrasonically treating and stirring for 45 minutes to form a polyester resin coating;
[0029] The mass ratio of the hard segment monomer, the soft segment monomer, the esterification catalyst, the polycondensation catalyst and the filler is 30:55:0.5:0.5:6.
[0030] The hard segment monomers in step (1) are terephthalic acid, sulfonated terephthalic acid and diol; the sulfonated terephthalic acid is sodium 5-sulfoisophthalate, and the diol is one of ethylene glycol, 1,4-butanediol and neopentyl glycol; the mass ratio of terephthalic acid, sulfonated terephthalic acid and diol is 1:0.3:0.8.
[0031] The soft segment monomers in step (1) are polyethylene glycol and adipic acid; the mass ratio of polyethylene glycol to adipic acid is 1:0.1.
[0032] The esterification catalyst in step (1) is 98% concentrated sulfuric acid.
[0033] During the esterification reaction in step (1), water produced by the reaction is continuously removed by vacuum distillation or by using a water separator to promote the esterification reaction.
[0034] The polycondensation catalyst in step (2) is Sb2O3; and the vacuum pressure is 500Pa.
[0035] In step (3), the filler is nano-silicon dioxide; and the solvent is butanone.
[0036] Example 2
[0037] A method for preparing a polyester resin coating for improving film adhesion comprises the following steps:
[0038] (1) adding a hard segment monomer and a soft segment monomer into a reaction kettle respectively, adding an esterification catalyst and heating to 180° C. to carry out an esterification reaction for 8 hours to form a hard segment prepolymer and a soft segment prepolymer respectively;
[0039] (2) adding a polycondensation catalyst to the hard segment prepolymer and the soft segment prepolymer, mixing them uniformly in a vacuum, and heating them to 230° C. for polycondensation for 4 hours to form a polyester resin;
[0040] (3) cooling to 120° C., adding fillers and solvents, ultrasonically treating and stirring for 30 minutes to form a polyester resin coating;
[0041] The mass ratio of the hard segment monomer, the soft segment monomer, the esterification catalyst, the polycondensation catalyst and the filler is 20:45:0.1:0.1:4.
[0042] The hard segment monomers in step (1) are terephthalic acid, sulfonated terephthalic acid and diol; the sulfonated terephthalic acid is 5-sodium sulfoisophthalate, and the diol is 1,4-butanediol; the mass ratio of terephthalic acid, sulfonated terephthalic acid and diol is 1:0.2:0.6.
[0043] The soft segment monomers in step (1) are polyethylene glycol and adipic acid; the mass ratio of polyethylene glycol to adipic acid is 1:0.08.
[0044] The esterification catalyst in step (1) is p-toluenesulfonic acid.
[0045] During the esterification reaction in step (1), water produced by the reaction is continuously removed by vacuum distillation or by using a water separator to promote the esterification reaction.
[0046] The polycondensation catalyst in step (2) is Sb(Ac)3; and the vacuum pressure is 100Pa.
[0047] In step (3), the filler is nano-silicon dioxide; and the solvent is toluene.
[0048] Example 3
[0049] A method for preparing a polyester resin coating for improving film adhesion comprises the following steps:
[0050] (1) adding a hard segment monomer and a soft segment monomer into a reaction kettle respectively, adding an esterification catalyst and heating to 220° C. to carry out an esterification reaction for 8 hours to form a hard segment prepolymer and a soft segment prepolymer respectively;
[0051] (2) adding a polycondensation catalyst to the hard segment prepolymer and the soft segment prepolymer, mixing them uniformly in a vacuum, and heating them to 280° C. for polycondensation for 4 hours to form a polyester resin;
[0052] (3) cooling to 150° C., adding fillers and solvents, ultrasonically treating and stirring for 60 minutes to mix evenly to form a polyester resin coating;
[0053] As a preferred technical solution of the present invention, the mass ratio of the hard segment monomer, the soft segment monomer, the esterification catalyst, the polycondensation catalyst and the filler is 40:65:1:1:8.
[0054] The hard segment monomers in step (1) are terephthalic acid, sulfonated terephthalic acid and diol; the sulfonated terephthalic acid is sodium 5-sulfoisophthalate, and the diol is neopentyl glycol; the mass ratio of terephthalic acid, sulfonated terephthalic acid and diol is 1:0.4:0.9.
[0055] The soft segment monomers in step (1) are polyethylene glycol and adipic acid; the mass ratio of polyethylene glycol to adipic acid is 1:0.15.
[0056] The esterification catalyst in step (1) is phosphoric acid.
[0057] During the esterification reaction in step (1), water produced by the reaction is continuously removed by vacuum distillation or by using a water separator to promote the esterification reaction.
[0058] The polycondensation catalyst in step (2) is antimony ethylene glycol; and the vacuum pressure is 1000 Pa.
[0059] In step (3), the filler is nano zinc oxide; and the solvent is acetone.
[0060] Example 4
[0061] A method for preparing a polyester resin coating for improving film adhesion comprises the following steps:
[0062] (1) adding a hard segment monomer and a soft segment monomer into a reaction kettle respectively, adding an esterification catalyst and heating to 190° C. to carry out an esterification reaction for 7 hours to form a hard segment prepolymer and a soft segment prepolymer respectively;
[0063] (2) adding a polycondensation catalyst to the hard segment prepolymer and the soft segment prepolymer, mixing them uniformly in a vacuum, and heating them to 240° C. for polycondensation for 9 hours to form a polyester resin;
[0064] (3) Cooling to 130° C., adding fillers and solvents, ultrasonically treating and stirring for 50 minutes to form a polyester resin coating.
[0065] The mass ratio of the hard segment monomer, the soft segment monomer, the esterification catalyst, the polycondensation catalyst and the filler is 30:50:0.2:0.2:5.
[0066] The hard segment monomers in step (1) are terephthalic acid, sulfonated terephthalic acid and diol; the sulfonated terephthalic acid is sodium 5-sulfoisophthalate, and the diol is ethylene glycol; the mass ratio of terephthalic acid, sulfonated terephthalic acid and diol is 1:0.3:0.7.
[0067] The soft segment monomers in step (1) are polyethylene glycol and adipic acid; the mass ratio of polyethylene glycol to adipic acid is 1:0.09.
[0068] The esterification catalyst in step (1) is 98% concentrated sulfuric acid.
[0069] During the esterification reaction in step (1), water produced by the reaction is continuously removed by vacuum distillation or by using a water separator to promote the esterification reaction.
[0070] The polycondensation catalyst in step (2) is GeO2; and the vacuum pressure is 200Pa.
[0071] The filler in step (3) is nano zinc oxide; and the solvent is a mixed solvent of toluene and butanone.
[0072] Example 5
[0073] A method for preparing a polyester resin coating for improving film adhesion comprises the following steps:
[0074] (1) adding a hard segment monomer and a soft segment monomer into a reaction kettle respectively, adding an esterification catalyst and heating to 210° C. to carry out an esterification reaction for 4 hours to form a hard segment prepolymer and a soft segment prepolymer respectively;
[0075] (2) adding a polycondensation catalyst to the hard segment prepolymer and the soft segment prepolymer, mixing them uniformly in a vacuum, and heating them to 270° C. for polycondensation for 5 hours to form a polyester resin;
[0076] (3) Cooling to 140° C., adding fillers and solvents, ultrasonically treating and stirring for 40 minutes to form a polyester resin coating.
[0077] The mass ratio of the hard segment monomer, the soft segment monomer, the esterification catalyst, the polycondensation catalyst and the filler is 35:60:0.8:0.8:7.
[0078] The hard segment monomers in step (1) are terephthalic acid, sulfonated terephthalic acid and diol; the sulfonated terephthalic acid is 5-sodium sulfoisophthalate, and the diol is 1,4-butanediol; the mass ratio of terephthalic acid, sulfonated terephthalic acid and diol is 1:0.4:0.8.
[0079] The soft segment monomers in step (1) are polyethylene glycol and adipic acid; the mass ratio of the polyethylene glycol to adipic acid is 1:0.14.
[0080] The esterification catalyst in step (1) is p-toluenesulfonic acid.
[0081] During the esterification reaction in step (1), water produced by the reaction is continuously removed by vacuum distillation or by using a water separator to promote the esterification reaction.
[0082] The polycondensation catalyst in step (2) is Sb2O3; and the vacuum pressure is 800Pa.
[0083] In step (3), the filler is nano-silicon dioxide; and the solvent is butyl acetate.
[0084] Comparative Example 1
[0085] On the basis of Example 1, the hard segment monomers were changed to terephthalic acid and ethylene glycol, the mass ratio of terephthalic acid to ethylene glycol was 1.3:0.8, and the rest was consistent with Example 1.
[0086] Comparative Example 2
[0087] Based on Example 1, no filler is added, and the rest is consistent with Example 1.
[0088] Performance Test:
[0089] The polyester resin coatings obtained in Examples 1-5 and Comparative Examples 1-2 were respectively applied on 50 μm PET films. During coating, care was taken to keep the dry coating amount of the coating at 1 to 2 μm. After drying, the adhesion test was performed according to standard GB / T 9286-2021. The smaller the grade, the better the adhesion.
[0090]
[0091]
[0092] The test results show that the adhesion of polyester resin coating can be improved by introducing sulfonated terephthalic acid and adding fillers.
[0093] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any indirect modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a polyester resin coating for improving film adhesion, characterized in that: The following steps are involved: (1) adding a hard segment monomer and a soft segment monomer into a reaction kettle respectively, adding an esterification catalyst and heating to 180-220° C. to carry out an esterification reaction for 3-8 hours to form a hard segment prepolymer and a soft segment prepolymer respectively; (2) adding a polycondensation catalyst to the hard segment prepolymer and the soft segment prepolymer, mixing them uniformly in a vacuum, and heating them to 230-280° C. for polycondensation for 4-10 hours to form a polyester resin; (3) Cooling to 120-150° C., adding fillers and solvents, ultrasonically treating and stirring for 30-60 minutes to form a polyester resin coating.
2. The method for preparing a polyester resin coating for improving film adhesion according to claim 1, characterized in that: The mass ratio of the hard segment monomer, the soft segment monomer, the esterification catalyst, the polycondensation catalyst and the filler is 20-40:45-65:0.1-1:0.1-1:4-8.
3. The method for preparing a polyester resin coating for improving film adhesion according to claim 1, characterized in that: The hard segment monomers in step (1) are terephthalic acid, sulfonated terephthalic acid and diol; the sulfonated terephthalic acid is sodium 5-sulfoisophthalate, and the diol is one of ethylene glycol, 1,4-butanediol and neopentyl glycol; the mass ratio of terephthalic acid, sulfonated terephthalic acid and diol is 1:0.2-0.4:0.6-0.
9.
4. The method for preparing a polyester resin coating for improving film adhesion according to claim 1, characterized in that: The soft segment monomers in step (1) are polyethylene glycol and adipic acid; the mass ratio of the polyethylene glycol to adipic acid is 1:0.08-0.
15.
5. The method for preparing a polyester resin coating for improving film adhesion according to claim 1, characterized in that: The esterification catalyst in step (1) is one of 98% concentrated sulfuric acid, p-toluenesulfonic acid and phosphoric acid.
6. The method for preparing a polyester resin coating for improving film adhesion according to claim 1, characterized in that: During the esterification reaction in step (1), water produced by the reaction is continuously removed by vacuum distillation or by using a water separator to promote the esterification reaction.
7. The method for preparing a polyester resin coating for improving film adhesion according to claim 1, characterized in that: The polycondensation catalyst in step (2) is one of Sb2O3, Sb(Ac)3, antimony glycol, and GeO2; and the vacuum pressure is 100-1000Pa.
8. The method for preparing a polyester resin coating for improving film adhesion according to claim 1, characterized in that: The filler in step (3) is nano silicon dioxide or nano zinc oxide; the solvent is one or more of toluene, acetone, butanone, and butyl acetate.
Citation Information
Patent Citations
Method for preparing polyester-polyester blocked copolyester
CN102516517A
Water-soluble polyester for textile size and preparation method of water-soluble polyester
CN102604062A
Two-step feeding synthesis method of high-performance poly(ether ester) elastomer
CN104371094A
Waterborne resin antifogging coating special for films and antifogging film
CN108084853A
Method for preparing water-based elastic polyester emulsion
CN109517192A